Simulación con dinámica molecular de las propiedades vibracionales de cintas de grafeno (2021)
Molecular Dynamics is a model that has become essential nowadays for the study of the physicochemical properties of different materials in nanometric and microscopic scales, it gives us accurate results that are necessary for comparison with the experimental research. LAMMPS (Large-scale Atomic/Molecular Massively ParallelSimulator) is a software that use Molecular Dynamics to model different atomic systems in a simple way. The main target of this research is to prove that the Molecular Dynamics model works, using theorical results of a nanoribbon and doing a vibrational analysis through density models of the vibrational states to find the characteristic peak of the C=C bond in the nanoribbon. It was found that this characteristic peak was about 1560.8 to 1629.1 1/cm which proves the accuracy of this model. Furthermore, the dependence of the position of the characteristic peak with the temperature was studied, with results that would be interesting to understand in future studies.